Optimization of pulsed vacuum osmotic dehydration of the cape gooseberry (Physalis peruviana L.) using the response surface methodology (2016)
ABSTRACT: The objective of this study was to optimize mass transfer during pulsed vacuum osmotic dehydration (PVOD) of cape gooseberries (Physalis peruviana L.) by means of the surface response methodology. The effects of the factors temperature (25-45°C), solids (50-70°Brix), rotation speed (60-100 rpm), pressure (50-100 mbar) and number of vacuum pulses (1-3) on osmotic dehydration, weight reduction percentage (WR), water loss percentage (WL), and solid gain percentage (SG%) were assessed. Sucrose syrup at a 5/1 syrup/fruit ratio was used for 2 h. The results provided 45°C, 70°Brix, 99.99 rpm, 98.92 mbar and 2.87 pulse vacuum, for a WR of47.52%, WL of 21.12%, and SG of 118.40% as the optimal conditions. Mathematic models were adjusted to the optimal conditions to describe the PVOD kinetics of cape gooseberries. Azuara's penetration empiric model, a phenomenological model from the solution of Fick's second law, and Peleg's empiric model were used. The latter adjusted better to the experiment data.